A novel organotypic cortical slice culture model for traumatic brain injury: molecular changes induced by injury and mesenchymal stromal cell secretome treatment - Pischiutta, Francesca; Cavaleiro, Helena; Caruso, Enrico; Tribuzio, Francesca; Di Marzo, Noemi; Moro, Federico; Kobeissy, Firas; Wang, Kevin K.; Salgado, António J.; Zanier, Elisa R. (Frontiers in Cellular Neuroscience, 2023)
Traumatic brain injury (TBI) is a major worldwide neurological disorder with no neuroprotective treatment available. Three-dimensional (3D) in vitro models of brain contusion serving as a screening platform for drug testing are lacking. Here we developed a new in vitro model of brain contusion on organotypic cortical brain slices and tested its responsiveness to mesenchymal stromal cell (MSC) derived secretome. A focal TBI was induced on organotypic slices by an electromagnetic impactor. Compared to control condition, a temporal increase in cell death was observed after TBI by propidium iodide incorporation and lactate dehydrogenase release assays up to 48h post-injury. TBI induced gross neuronal loss in the lesion core, with disruption of neuronal arborizations measured by microtubule-associated protein-2 (MAP-2) immunostaining and associated with MAP-2 gene down-regulation. Neuronal damage was confirmed by increased levels of neurofilament light chain (NfL), microtubule associated protein (Tau) and ubiquitin C-terminal hydrolase L1 (UCH-L1) released into the culture medium 48h after TBI. We detected glial activation with microglia cells acquiring an amoeboid shape with less ramified morphology in the contusion core. MSC-secretome treatment, delivered 1h post-injury, reduced cell death in the contusion core, decreased NfL release in the culture media, promoted neuronal reorganization and improved microglia survival/activation. Our 3D in vitro model of brain contusion recapitulates key features of TBI pathology. We showed protective effects of MSC-secretome, suggesting the model stands as a tractable medium/high throughput, ethically viable, and pathomimetic biological asset for testing new cell-based therapies.